PERANCANGAN PROTOTYPE MAINAN ALAT BERAT MENGGUNAKAN CREO 2.0 - , FARID NOVIAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of product in recently is getting increase especially in design sector. For getting the new product with high quality must be followed with good product design. When the product is crucial then the design is complicated too. This case make the programmer or scientist created come engineering software such as AutoCAD, Master CAM, Inventor, Pro/ENGINEER, SOLIDWORKS, and CREO. With this software, the scientist in technolgy information hope this software would be helping in design a complicated product and make easier for engineering when finish part of product The Authorâs final project is to design a toy using CREO Parametric software. In this report, author described how design of a toyâs part can be made sed CREO. After every parts designed, then it is assembled so that form of the toy is shown. When designed the parts, some part need high precision. The purpose is when assembling these part, each of part conected perfectly. After performing the methods described earlier, then finalized the report containing the process step by step the use of Creo in design of a toy. The results of Creo is make the proscess part more simple an easier.